Characterization of bioactive compounds extracted from patchouli : Comparing microwave-assisted hydrodistillation and hydrodistillation methods - Azhari, Hamid Nour; Sundarajan, Siva (IOP Publishing Ltd, 2019)
Microwave-assisted hydrodistillation (MAHD) is a promising and advanced technology that uses microwave heating to extract essential oils from dry leaves. Currently available conventional methods are time consuming, thermally unsafe and require costly solvents. In the current study, MAHD and traditional hydrodistillation (HD) techniques were compared and their effectiveness in the separation of the essential oil from dry patchouli leaves have been studied. The patchouli oil that obtained from MAHD and HD extraction methods were characterized using gas chromatography-mass spectrometry (GC-MS) analysis and the impact of the two extraction methods on the plant morphology were observed using scanning electron microscopy (SEM) analysis. The results indicated that MAHD method extracted 5 % of essential oil at solid to solvent ratio of 1:12 g/ml from patchouli leaves as compared to 4 % obtained using HD method at 45 minutes of extraction time. In addition, MAHD method can retain 16 compounds while only 11 chemical compounds were extracted using HD. Thus, MAHD showed a greater potential for better production of the essential oil from patchouli leaves as compared to HD method.